2022
DOI: 10.1302/0301-620x.104b7.bjj-2021-1765.r1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of capsular preservation on patient-reported outcomes and complication rates in total hip arthroplasty using the direct anterior approach

Abstract: Aims It is not known whether preservation of the capsule of the hip positively affects patient-reported outcome measures (PROMs) in total hip arthroplasty using the direct anterior approach (DAA-THA). A recent randomized controlled trial found no clinically significant difference at one year postoperatively. This study aimed to determine whether preservation of the anterolateral capsule and anatomical closure improve the outcome and revision rate, when compared with resection of the anterolateral capsule, at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Although all patients in present study had no early postoperative dislocations, it cannot be concluded whether the dislocation rate is reduced by anterior capsular suture. In previous studies, no differences of dislocation rate were found between resection or preservation of the anterior capsule in DAA-THA 21 , 23 . However, these studies did not take into account the degree of hip laxity before the suture, and the cases that did not have hip laxity before the suture could be included.…”
Section: Discussionmentioning
confidence: 79%
“…Although all patients in present study had no early postoperative dislocations, it cannot be concluded whether the dislocation rate is reduced by anterior capsular suture. In previous studies, no differences of dislocation rate were found between resection or preservation of the anterior capsule in DAA-THA 21 , 23 . However, these studies did not take into account the degree of hip laxity before the suture, and the cases that did not have hip laxity before the suture could be included.…”
Section: Discussionmentioning
confidence: 79%